Exploring sustaining embodied experience in the built environment: a case study of Seonyudo - Sanghee Lee (Journal of Asian Architecture and Building Engineering)
This study adopts a multidisciplinary approach, integrating the embodied experience framework with insights from embodied cognition and contextual design methodology, to investigate human interactions within a sustainable urban park. Focused on a post-industrial setting, it aims to validate the embodied experience process and identify key elements of sustainable urban environments. Through an empirical approach, this research seeks to deepen understanding of human engagement with built environments, enhancing awareness and communication around sustainable design concepts. Findings uncover diverse narratives of embodied experiences, structured by five contextual design models: (1) Flow model, mapping information flow; (2) Sequential model, outlining experience-influencing elements; (3) Artifact model, identifying experience-amplifying mediums; (4) Spatial model, showing relationships between artificial and natural environments; and (5) Cultural model, highlighting environment types in cultural contexts. This approach provides insights into urban sustainability’s experiential aspects, promoting a deeper understanding of embodied experiences and their role in sustainable design. It contributes to designing sustainable urban environments, linking theory with practical applications to improve urban life quality in sustainability initiatives.